The Quality of Learning Environment and Academic Performance from a Student’s Perception - Kamaruddin, Rohana; Zainal, Nor Rashidah; Mohd Aminuddin, Zaidi; Jusoff, Kamaruzaman (2009)
The study determined how students assess the various components of their learning environment. It also identified how the learning environment affects students' learning outcomes. A sample of 370 randomly selected students was taken from a population of Bumiputera’s students. Data analysis was done using descriptive statistics and Product Moment Correlation. Findings revealed that students could assess the four components that contribute to their academic performance, which is: facilities provided (11 items), housing environment, parents motivation, school and teacher factors. Housing environment and parent’s motivation has the highest assessment while facilities provided at home have the least. The results also showed that only two components of the learning environment are positively correlated with students' academic performance that is housing environment and school/teacher involvement. The findings are discussed with a view to improve the quality of the learning environment, subsequent academic performance.